Predictors of self-perceived cultural responsiveness in entry-level physiotherapy students in Australia and Aotearoa New Zealand - Te, M.; Blackstock, F.; Fryer, C.; Gardner, Peter; Geary, L.; Kuys, S.; McPherson, K.; Nahon, I.; Tang, C.; Taylor, L.; Van Kessel, G.; van der Zwan, K.; et al. (BioMed Central Ltd., 2019)
Background: Ensuring physiotherapy students are well prepared to work safely and effectively in culturally diverse societies upon graduation is vital. Therefore, determining whether physiotherapy programs are effectively developing the cultural responsiveness of students is essential. This study aimed to evaluate the level of self-perceived cultural responsiveness of entry level physiotherapy students during their training, and explore the factors that might be associated with these levels. Methods: A cross sectional study of physiotherapy students from nine universities across Australia and Aotearoa New Zealand was conducted using an online self-administered questionnaire containing three parts: The Cultural Competence Assessment tool, Altemeyer’s Dogmatism scale, and the Marlowe-Crowne social desirability scale- short form. Demographic data relating to university, program, and level of study were also collected. Data was analysed using one-way ANOVA, t-tests and multiple regression analysis. Results: A total of 817 (19% response rate) students participated in this study. Overall, students had a moderate level of self-perceived cultural responsiveness (Mean (SD) = 5.15 (0.67)). Fewer number of weeks of clinical placement attended, lower levels of dogmatism, and greater social desirability were related to greater self-perceived cultural responsiveness. Additionally, fourth year undergraduate students perceived themselves to be less culturally responsive than first and second year students (p < 0.05). Conclusions: These results provide educators with knowledge about the level of self-perceived cultural responsiveness in physiotherapy students, and the factors that may need to be assessed and addressed to support the development of culturally responsive practice.